2016
DOI: 10.15376/biores.11.3.7462-7475
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Adsorbable Organic Halides (AOX) Reduction in Laccase-Aided Chlorine Dioxide Bleaching of Bagasse Pulp

Abstract: This paper presents a kinetic model of the laccase-aided chlorine dioxide bleaching of bagasse pulp. The kinetic model was based on the rate of reduction of adsorbed organic halogen (AOX). The effects of the laccase enzyme dosage, the mediator 1-hydroxybenzotriazole (HBT) dosage, and the reaction temperature on the AOX content of the bleaching effluent are discussed. Good fits were obtained for the experimental data obtained from the different laccase enzyme dosages, HBT dosages, and reaction temperatures, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…11 Song et al constructed the kinetics of laccase-aided chlorine dioxide bleaching and discussed the effects of laccase dosage, hydrogen peroxide dosage, and reaction temperature on the AOX content. 12 Other researchers developed kinetic models of the first or second chlorine dioxide bleaching stage to analyze the factors influencing the reaction rate of AOX. 13−15 kinetic model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Song et al constructed the kinetics of laccase-aided chlorine dioxide bleaching and discussed the effects of laccase dosage, hydrogen peroxide dosage, and reaction temperature on the AOX content. 12 Other researchers developed kinetic models of the first or second chlorine dioxide bleaching stage to analyze the factors influencing the reaction rate of AOX. 13−15 kinetic model.…”
Section: Introductionmentioning
confidence: 99%
“…Lei et al investigated the kinetics and mechanisms for the delignification of ClO 2 in an aqueous solution by 5,5′-diallyl-2,2′-dihydroxy-3,3′-dimethoxybiphenyl . Song et al constructed the kinetics of laccase-aided chlorine dioxide bleaching and discussed the effects of laccase dosage, hydrogen peroxide dosage, and reaction temperature on the AOX content . Other researchers developed kinetic models of the first or second chlorine dioxide bleaching stage to analyze the factors influencing the reaction rate of AOX. These studies have shown that AOX emissions can be predicted by the kinetic model of AOX formation, and the AOX emission can be decreased by adjusting the operating conditions based on the kinetic model.…”
Section: Introductionmentioning
confidence: 99%